A Software-Defined Channel Sounder for Industrial Environments with Fast Time Variance - Fliedner, Niels Hendrik; Block, Dimitri; Meier, Uwe (arXiv:1805.01236)
Novel industrial wireless applications require wideband, real-time channel characterization due to complex multipath propagation. Rapid machine motion leads to fast time variance of the channel's reflective behavior, which must be captured for radio channel characterization. Additionally, inhomogeneous radio channels demand highly flexible measurements. Existing approaches for radio channel measurements either lack flexibility or wide-band, real-time performance with fast time variance. In this paper, we propose a correlative channel sounding approach utilizing a software-defined architecture. The approach enables real-time, wide-band measurements with fast time variance immune to active interference. The desired performance is validated with a demanding industrial application example.
Keywords: Correlation; Wireless communication; Real-time systems; Logic gates; Frequency measurement; Libraries; Time measurement